Tracking and Mapping of Spatiotemporal Quantities Using Unicellular Swarm Intelligence Visualisation of Invisible Hazardous Substances Using Unicellular Swarm Intelligence - Oyekan, John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The book discusses new algorithms capable of searching for, tracking, mapping and providing a visualization of invisible substances. It reports on the realization of a bacterium-inspired robotic controller that can be used by an agent to search for any environmental spatial function such as temperature or pollution. Using the parameters of a mathematical model, the book shows that it is possible to control the exploration, exploitation and sensitivity of the agent. This feature sets the work apart from the usual method of applying the bacterium behavior to robotic agents. The book also discusses how a computationally tractable multi-agent robotic controller was developed and used to track as well as provide a visual map of a spatio-temporal distribution of a substance. On the one hand, this book provides biologists and ecologists with a basis to perform simulations related to how individual organisms respond to spatio-temporal factors in their environment as well as predict and analyze the behavior of organisms at a population level. On the other hand, it offers robotic engineers practical and fresh insights into the development of computationally tractable algorithms for spatial exploratory and mapping robots. It also allows a more general audience to gain an understanding of the design of computational intelligence algorithms for autonomous physical systems.
Introduction -- Literature Review -- Investigative Process -- Developing and Implementing a Source Finding Controller -- Relationship between the Berg-Brown Model and the Keller-Segel Model -- Behaviour Based Coverage Controller -- Improvements and towards RealWorld Applications -- Conclusion.
Keywords: Control engineering; Robotics; Automation; Dynamics; Nonlinear theories; Environmental engineering; Biotechnology; Bioremediation; Microbiology; System theory; Mathematical physics; Control, Robotics, Automation; Applied Dynamical Systems; Environmental Engineering/Biotechnology.; Microbiology; Complex Systems; Theoretical, Mathematical and Computational Physics